1996
DOI: 10.4319/lo.1996.41.6.1347
|View full text |Cite
|
Sign up to set email alerts
|

Application of 222Rn and CH4 for assessment of groundwater discharge to the coastal ocean

Abstract: Groundwater discharge is a neglected source of freshwater and dissolved constituents to the ocean. It can occur via diffuse seepage and point source spring discharge. Two naturally occurring trace gases, 222Rn and CH4, are present in groundwater at concentrations that are elevated by several orders of magnitude relative to seawater, and they may be useful in tracing groundwater inputs to surface waters. Water samples collected near a submarine spring in the northeastern Gulf of Mexico displayed radon and metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(81 citation statements)
references
References 12 publications
5
73
1
1
Order By: Relevance
“…While we do not have detailed information about currents in the reef for the study period, the diurnal tidal range was from 0.6 to 1.1 m during the time of the December period of the study indicating that the reef is well-flushed since the average depth is ∼ 2 m. Since there is no surface drainage on the north side of Santiago Island and since 222 Rn was not detected beyond the reef crest in the open ocean, the 222 Rn inventory in the reef is very likely due to SGD. Although our estimated 222 Rn diffusive flux from sediment is much smaller than Cable et al [1996aCable et al [ , 1996b, our total bottom water 222 Rn concentrations are similar to those at their sites (∼1-2 dpm/L but sometimes as high as 4 dpm/L) where they estimated SGD to have a magnitude of several cm/d over hundreds of square kilometers.…”
Section: Radonmentioning
confidence: 60%
See 1 more Smart Citation
“…While we do not have detailed information about currents in the reef for the study period, the diurnal tidal range was from 0.6 to 1.1 m during the time of the December period of the study indicating that the reef is well-flushed since the average depth is ∼ 2 m. Since there is no surface drainage on the north side of Santiago Island and since 222 Rn was not detected beyond the reef crest in the open ocean, the 222 Rn inventory in the reef is very likely due to SGD. Although our estimated 222 Rn diffusive flux from sediment is much smaller than Cable et al [1996aCable et al [ , 1996b, our total bottom water 222 Rn concentrations are similar to those at their sites (∼1-2 dpm/L but sometimes as high as 4 dpm/L) where they estimated SGD to have a magnitude of several cm/d over hundreds of square kilometers.…”
Section: Radonmentioning
confidence: 60%
“…We analyzed 222 Rn in bottom waters along the reef following the approach described in Burnett and Dulaiova [2003] using the RAD-7 portable radon-in-air monitor (Durridge Co. Inc.) and also ran sediment equilibration experiments for several weeks to determine 222 Rn diffusive flux from the sediment similar to Cable et al [1996b]). In-situ measurements ( Figure 1 …”
Section: Measurements Of 222 Rnmentioning
confidence: 99%
“…Locally, groundwater inputs to the coastal zone can have major effects on geochemical cycles either through the discharge of fresh groundwater or the recirculation of seawater through shoreline aquifers (Buddemeier, 1996;Moore, 1997Moore, , 1999. SGD is now recognized as a potentially important pathway for pollution migration to the nearshore, particularly where agricultural or urban activities have impacted the groundwater (Cable et al, 1996;Corbett et al, 1999, Kelley andMoran, 2002;Boehm et al, 2004). Because 37% of the world's population lives within 100 km of the coastal zone (Cohen et al, 1997), understanding the increasing effects of the ever-growing human population on the coastal environment is critical to development of sound management principles.…”
Section: Article In Pressmentioning
confidence: 99%
“…It is, however, challenging to separate the respective contributions of FSGD and saline SGD (i.e., seawater recirculation) to total SGD even with the use of multiple tracers (radon, radium, methane, salinity, etc.) [e.g., Cable et al, 1996;Santos et al, 2009b;Santos et al, 2009c]. Large discrepancies between tracer-based and inland hydrology-based estimates (e.g., seepage meters, water budgets) of FSGD are still often observed [Destouni and Prieto, 2010] in part because different techniques quantify different components of SGD.…”
Section: Rechargementioning
confidence: 99%
“…As such SGD may be an important greenhouse gas source. Early investigations used CH4 as a tracer of SGD Cable et al, 1996] and revealed significant correlations between CH4…”
mentioning
confidence: 99%